2023
DOI: 10.1002/epd2.20069
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological aspects of antiseizure medications: From basic mechanisms to clinical considerations of drug interactions and use of therapeutic drug monitoring

Abstract: Antiseizure medications (ASMs) are the cornerstone of treatment for patients with epilepsy. Several new ASMs have recently been introduced to the market, making it possible to better tailor the treatment of epilepsy, as well as other indications (psychiatry and pain disorders). For this group of drugs there are numerous pharmacological challenges, and updated knowledge on their pharmacodynamic and pharmacokinetic properties is, therefore, crucial for an optimal treatment outcome. This review focuses on educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 93 publications
1
6
0
Order By: Relevance
“…28,30 This approach is also important with the present drug, which is mainly used for children, for whom physiological changes affect the pharmacokinetics of drugs, leading to increased clearance in children younger than 6 years. 15,31 May et al 6 also found a need for higher dose/kg weight in younger patients ( younger than 14 years) and that most patients use doses <600 mg/d, as in the present study, in which most patients used <400 mg/d. This age-related finding in C/D ratios suggests the usefulness of regular sulthiame measurement to adjust the dosage for variability in pharmacokinetics.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…28,30 This approach is also important with the present drug, which is mainly used for children, for whom physiological changes affect the pharmacokinetics of drugs, leading to increased clearance in children younger than 6 years. 15,31 May et al 6 also found a need for higher dose/kg weight in younger patients ( younger than 14 years) and that most patients use doses <600 mg/d, as in the present study, in which most patients used <400 mg/d. This age-related finding in C/D ratios suggests the usefulness of regular sulthiame measurement to adjust the dosage for variability in pharmacokinetics.…”
Section: Discussionsupporting
confidence: 79%
“…To elucidate the possible impact of ASM comedication on sulthiame pharmacokinetics, patients were divided into different categories based on coprescribed ASMs, as in previous studies: strong enzyme inducers (carbamazepine, phenobarbital, primidone, and phenytoin), weak enzyme inducers (oxcarbazepine and eslicarbazepine), valproate as a potential enzyme inducer or inhibitor, and clobazam as a possible enzyme inducer. 15,18–22 None of the included patients were instructed to use any other types of drugs with known inducing or inhibiting properties of CYP enzymes. Comedication with ASMs and other drugs considered neutral served as the comparator group, and these patients could not use drugs from other categories.…”
Section: Methodsmentioning
confidence: 99%
“…TDM is applied to a wide range of drugs administered in various pathological conditions, such as immunosuppressive drugs used in transplantation or for the treatment of inflammatory bowel disease and autoimmune hepatitis [ 21 ], antifungal agents [ 22 ], antibiotics administered in critically ill patients [ 9 ] or in bacterial infections [ 23 ], antiepileptics [ 24 ], and anticancer drugs [ 4 ]. The main categories of drugs measured in 2003 and 2021 in Greece were antiepileptics, psychiatric drugs, analgesics, immunosuppressants, and antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Others, for example, cannabidiol and cenobamate, have been shown to have additional mechanisms of anticonvulsant action. 2 Generally, “traditional” sodium channel blockers have similar efficacy in controlling focal seizures with some being additionally used for treating generalized epilepsies. 1 The scope of activity has not been fully established for the newer sodium blockers, but their adverse effect profiles might differ from those of older drugs (eg, with regard to sleepiness 3 or induction of drug-metabolizing enzymes).…”
Section: Commentarymentioning
confidence: 99%